Design of Working Facilities Based on Posture Risk Assessment and Anthropometry - Nofierni, Nofierni; Patmawati, Debby; Aunurrofiq, Fadli (Universitas Al Azhar Indonesia, 2025)
The operators on assembly lines are complaining about pain in their muscle and joints when carrying out work. This study aimed to assess posture risk on assembly line with manual work, and propose appropriate design for work station facilities. The research was conducted to operators in the n transformer assembly lines. The method used to evaluate the working posture effort and risk was the combined Nordic Body Map and Rapid Upper Limb Assessment (RULA). Based on the RULA method, the operator's body position is at high risk with a score of seven (7), so immediate working corrections are needed. The current faulty design of work stations that are not in accordance with ergonomic principles causes work musculoskeletal disorder in wound core assembly line operators. Based on the lengthy analysis of the faulty operator postures in the wound core assembly, a new table and chair design was proposed. Keywords – Anthropometry, Ergonomics, Manual Work, Posture, Risk Assessment.